Concepção de um equipamento para o desponte e recolhimento das flores da planta de tabaco: contribuições para a mecanização da cultura - Marques, Jorge Luiz Rodrigues (2021)
Brazil currently produces around 460,000 tons of tobacco per year, ranking among the largest producers in the world. Since 1993, it has been the world's largest tobacco exporter, by volume. Tobacco cultivation is developed in more than 600 municipalities in the three states of the Southern Region. In rural areas alone, tobacco occupies more than 638,000 direct jobs — in addition, processing plants and cigarette factories employ more than 40,000 people. In this sense, a technically and economically viable alternative was sought for the use of tobacco seed for the production of aviation biofuel. So far there is no such use of seeds, which need to be removed through manual pruning. Mechanical technology is not available in the Brazilian market to assist agricultural producers in this arduous work, which is performed even in the traditional tobacco production crop. Several research projects are underway in several countries with the purpose of implementing the use of bioenergy in air transport. Aviation biokerosene is a fuel derived from renewable sources, and studies carried out show that it is feasible to obtain it from tobacco seed. The objective of this work is to develop equipment that cuts and collects the tobacco flower for further processing. Therefore, the fundamental characteristic of this equipment is the ability to cut and harvest only the plant's flowers, preserving the leaves, as they will regrowth, thus eliminating manual or chemical pruning used in the crop. The equipment allows the removal and collection of the upper part of the plant through a rotor mechanically driven by a hydraulic system. This system is mounted on a platform pulled by a micro tractor and which cuts the plant stalk and directs it towards the rear of the machine, depositing it on a mobile structure coupled to the machine, which allows for further processing. In tests carried out in the field, the equipment fulfilled the objective, having a very satisfactory result by simplifying and reducing the farmer's exposure time in the field, which is quite harmful to his health. This technology, when fully fulfilling its function, becomes viable for production by the metal-mechanical sector; there is, therefore, the possibility that it will be used in the development of a commercial product.